2015
DOI: 10.1080/14680629.2015.1064011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of additives on the microstructure of clay

Abstract: Some soils under construction cause numerous problems in terms of geotechnical engineering. Clay soils cause significant problems in the construction of roads, airports, pavements and highways. Some soils contain mixed additives, such as lime, cement, fly ash and bitumen. In this study, the microstructures of uncured and cured lime/cement-stabilised clay samples are investigated. Compacted soil samples were evaluated by mercury intrusion porosimetry, X-ray diffraction, scanning electron microscopy (SEM) analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 22 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…Lime treatment is usually used to improve the mechanical properties of fine-grained soils (Little, 1995;Prusinski & Bhattacharja, 1999;Parsons & Milburn, 2003;Al-Mukhtar et al, 2010;Tang et al, 2011;Wang et al, 2019). Actually, lime treatment of fine-grained soil creates cementitious compounds from pozzolanic reaction, coating the soil particles and bonding them together (Al-Mukhtar et al, 2012;Tran et al, 2014;Wang et al, 2015;Ural, 2016;Wang et al, 2016;Wang et al, 2017). In addition, the improvement depends on both lime content and curing time (Bell, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Lime treatment is usually used to improve the mechanical properties of fine-grained soils (Little, 1995;Prusinski & Bhattacharja, 1999;Parsons & Milburn, 2003;Al-Mukhtar et al, 2010;Tang et al, 2011;Wang et al, 2019). Actually, lime treatment of fine-grained soil creates cementitious compounds from pozzolanic reaction, coating the soil particles and bonding them together (Al-Mukhtar et al, 2012;Tran et al, 2014;Wang et al, 2015;Ural, 2016;Wang et al, 2016;Wang et al, 2017). In addition, the improvement depends on both lime content and curing time (Bell, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Similar works carried out by foreign researchers in particular dealing with the stabilization of clay soils of lowintensity roads with ash from burning coal are described in the following scientific paper [13]. A significant economic effect from the use of such design solutions is obvious.…”
Section: Introductionmentioning
confidence: 79%
“…Separately, a very promising direction of research which should be noted associated with the strengthening of soil foundations based on the use of cohesive soils with a compaction factor of 1.05 and higher. It is known that clay soils cause significant problems in road construction [13]. The use of repacking technology can significantly reduce the cost of building and maintaining the road pavement due to an obstacle to a capillary ascension of water [14].…”
Section: Introductionmentioning
confidence: 99%
“…The XRD and SEM analyses of compacted samples were performed. It was found that an increase in lime and cement content led to a more refined pore structure and this refinement increased with the increase in the curing period (Ural, 2016). Bhardwaj and Sharma (2020) tested natural soil at a depth of 1-1.5 meters from the ground surface with and without the addition of lime.…”
Section: Background Of Theorymentioning
confidence: 99%
“…The use of mineral additives to this type of soil can alleviate these problems. Ural (2016) examined the performance of clay when adding lime, cement and FA or other waste materials. The XRD and SEM analyses of compacted samples were performed.…”
Section: Background Of Theorymentioning
confidence: 99%